How can we exploit above–belowground interactions to assist in addressing the challenges of food security? - Orrell, Peter; Bennett, Alison E. (Frontiers in Plant Science, 2013)
Can above–belowground interactions help address issues of food security? We address this question in this manuscript, and review the intersection of above–belowground interactions and food security. We propose that above–belowground interactions could address three strategies identified by Godfray et al. (2010): Reducing the Yield Gap, Increasing Production Limits, and Reducing Waste. In particular, to minimise the difference between potential and realised production (The Yield Gap) above–belowground interactions could be manipulated to reduce losses to pests and increase crop growth (and therefore yields). To Reduce Waste above–belowground interactions can again be manipulated to reduce waste generated from in field losses. Finally, to Increase Production Limits we propose two mechanisms: utilizing intercropping (which uses multiple aspects of above–belowground interactions) and breeding for improved beneficial above–belowground interactions as well as breeding mutualistic organisms to improve their provided benefit. As a result, if they are managed correctly, there is great potential for above–belowground interactions to contribute to food security.